Variability of Selected Somatic Features of Women and Men in the Final Phases of Ontogenesis - Kriesel, Guido (Anthropological Review, 1987)
The studied material comprises measurements of500women and 500 men in the age from 60 to 95 years. The arithmetic averages and standard deviations of the investigated measurements with a division into age groups are given separately for women (Table 1) and men (Table 2). Analogical data referring to the calculated indices ire contained in Tables 3 and 4 respectively. Within the distinguished groups of men and women also the Correlation coefficients between the body stature and other measurements (Table 5) are calculated. The agedepending variability of sexual dimorphism is presented in the form of relative deviation percentages (Table 6). In women and men in the successive age groups, the arithmetic averages of the majority of measurements decrease, only the depth of chest increases. With age also the body proportions change. The length of the trunk diminishes in relation to body stature and lie length of limbs. The shoulders get raised in relation to body stature and jugular incisure. The thoracic kyphosis and the arithmetic averages of iliac, ilio-acromial and chest indices are increased. It is presumed that the values of correlation coefficients changing with age are a reflection of the differentia involutional changes which in both sexes lead to different effects? In women, with age the increasing values correlation coefficients indicate that the relations between the body stature and other investigated features become similar. On the other hand, in men the values of these coefficients decreasing with age: indicate increase differentiation of these proportions. It seems also that the degree of the advancement of the involutional changes higher in women than in men. In contrast to the value of correlation coefficients the sex dimorphism of the majority of measurements indices does not change significantly with age. Distinct age changes of sex dimorphism refer to the depth of chest the index of the upper limb.